Study of serum FT3, FT4 and TSH in pregnant women - Yeasmin, Shahanara; Hossain, AFM Anwar; Yeasmin, Tahmina; Amin, Md Ruhul; Akhter, Qazi Shamima; Kader, Md Abdul; Kamal, Mostafa (Journal of Dhaka Medical College, 2015)
Background: Thyroid diseases have a strong predominance in woman of childbearing age. Pregnancy may be associated with thyroid dysfunction. The aim of the present study was to assess the serum FT3, FT4 and TSH levels in pregnant women. Methods: This cross-sectional analytical study was done in the Department of Physiology of Dhaka Medical College, Dhaka, from July 2006 to June 2007. Total 50 apparently healthy women of low socioeconomic class, age ranged from 18-40 years were selected from the Outpatient Department of Urban Primary Health Care Project (UPHCP) at Mirpur, Dhaka. Out of them 30 pregnant women of different trimester were taken as study group (group A) and 20 age matched non pregnant women were taken as control (group B). Serum FT3, FT4 and TSH levels were parameters in both groups. Statistical analysis was done by the SPSS version 12.0. Results: The mean serum FT3 levels were 6.36±1.16 pmol/L and 6.381.36 pmol/L in group A (Study) and group B (control) respectively. The mean serum FT4 levels were 20.25±4.77 pmol/L and 19.39±8.17 pmol/L in group A (Study) and group B (control) respectively. The mean serum TSH levels were 0.96±0.96 mIu/L and 1.27±0.86 mIu/L in group A (Study) and group B (control) respectively. The difference was not significant (p>0.05) between group A and B. Conclusion: From the results obtained in the present study, it may be concluded that there is no change of serum FT3, FT4 and TSH level in pregnancy. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22697 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 68-72